Pengaruh Waktu Aging Terhadap Kristalinitas dan Ukuran Partikel Silika Mesopori - Fila Delvia; Syamsi Aini (Departemen Kimia FMIPA UNP, 2020)
Mesoporous silika with a pore diameter of 2-50 nm can be used in various fields such as adsorption, sensor, medicine, immobilization of metal nanoparticles in catalyst synthesis and stationary phase for chromatography. Mesoporous silika synthesis was carried out using sodium silicate form rijang stone West Sumatera. Mesoporous silica was synthesized using the sol-gel method. Synthesis was carried out to determine the effect of aging time (24 hours and 48 hours) on the crystallity and particle size of mesoporous silica. Mesoporous silica was characterized using XRD (X-Ray Difraction) to see the crystallinity of the silica and the crystal size of the resulting sample. The result of XRD data measurement showed tha the peaks appeared at a high angle of 2Ɵ=23o, a large mesoporous silica particle size and high crystallinity were obtained at 24 hours of aging.